Effective Strategy in Event Management of West Java Youth Digital Training Program - Putri, Shinta Hartini; Putri, Aura Amalllia; Dewi, Eriyanti Nurmala (Sinergi International Journal of Communication Sciences, 2024)
The West Java Youth Digital Training Program is a digital training program in West Java designed to improve the digital skills of young people. This study aims to identify the stages of implementation, obstacles, and reasons for the implementation of the West Java Youth Digital Training Program. This study utilizes a qualitative method with a case study approach, collecting primary data through interviews and observations, as well as secondary data from books, theses, and online sources. The study's informants were selected by purposive sampling, and source triangulation was used to ensure data validity. The results of this study indicate that the stages of organizing the West Java Youth Digital Training Program event include research, design, planning, coordinating, and evaluating. The research stage focuses on identifying the need for digital literacy among individuals aged 16 to 30. The design stage involves creating posters, selecting Jabar Digital Service as a resource person, and minimalist decorations. The planning stage encompasses biannual training sessions, material planning, and participant selection through motivation letters. The coordinating stage involves committee meetings, coordination of consumption with hotels, and communication of participants through WA Group. The evaluation stage involves enhancing the selection process, questionnaires, and the preparation of professional certification. The study identified several obstacles, including the low level of digitalization in West Java, limited public relations personnel, busy event schedules, and ineffective coordination. The primary rationale for implementing this program is to equip the younger generation of West Java with the necessary skills to thrive in the digital era.